Dimensions of knowledge management maturity: top management support and leadership, people, and information technology / Noreen Natasha Azmee, Norliya Ahmad Kassim and Che Zainab Haji Abdullah. - Azmee, Noreen Natasha; Ahmad Kassim, Norliya; Haji Abdullah, Che Zainab (Universiti Teknologi MARA Cawangan Selangor, 2017)
Knowledge management (KM) has been applied in many organizations such as government agencies, construction companies, universities and libraries. Assessing the KM maturity in organization is important to identify the current status of KM and areas of KM could be improved. Very little evidence exists regarding KM maturity specifically in academic libraries. In view of this gap, the main purpose of this paper is to explore the dimensions of KM maturity in academic libraries namely top management support and leadership, people and information technology. Further research is required to establish the relationship between KM maturity and organizational performance in academic libraries.